Confidence–Competence Mismatch and Reasons for Failure of Non-Medical Tourniquet Users. (2nd January 2017) - Baruch, Erez N.; Kragh, John F.; Berg, Amy L.; Aden, James K.; Benov, Avi; Shina, Avi; Shlaifer, Amir; Ahimor, Alon; Glassberg, Elon; Yitzhak, Avraham
Abstract: Objective: Tourniquet application is a lifesaving skill taught worldwide in first aid bleeding control courses. We observed performance among non-medical users of tourniquets in their confidence, competence, and reasons for failure.Methods: 179 Israeli military recruits without prior medical training underwent their standard first aid course where they learned Combat Application Tourniquet (CAT; Composite Resources, Rock Hill, SC, USA) use. After course completion, they self-reported confidence in tourniquet use. User performance was assessed 7–14 days later using a HapMed™ mannequin that assessed time, pressure, and blood loss. Competent performance required in aggregate: 1) use with pressure of 200 mmHg or more, 2) hemorrhage volume of less than 638 mL, and 3) correct placement of the tourniquet. For failed performance, a reason for failure was reported independently by both the user and an expert observer.Results: 45 of 179 user performances (25%) were competent. Users who reported high confidence had only a slightly higher chance of achieving competence in tourniquet application (r = 0.17, p = 0.022). The most common reason for failure was excess slack in the CAT's strap (experts 55%, users 39%), and too few turns of the windlass (23% and 31%, respectively) was the second most common reason. Expert and user evaluations had poor agreement (κ = 0.44, 95% CI 0.32–0.56).Conclusion: The most common reason for failed use of tourniquets among non-medical users was excess slack in the tourniquet strap. Users self-evaluated their performance inaccurately and demonstrated a confidence-competence mismatch. These pitfalls in performance may help tourniquet instructors improve training of caregivers.